Problem-based learning with library e-resources to enhance student information literacy self-efficacy - Prabowo, Thoriq Tri; Sitthiworachart, Jirarat; Hong, Jon Chao; Joy, Mike (My University, 2024)
Purpose: This study investigates the effectiveness of problem-based learning (PBL) in information literacy curricula using library e-resources to enhance information literacy self-efficacy (ILSE) of students in two universities in Indonesia, in Java Island (University A) and Sumatra Island (University B). Design/methodology/approach: A comparison of the effectiveness of the approach in the two universities forms the focus of the study, which has adopted a single group quasi-experimental design which was conducted in one online teaching-learning session. The authors compared the pre-test and post-test scores of 65 library and information science (LIS) students from both universities. Findings: The results show that the treatment enhanced ILSE effectively. After the treatment, University A students performed better than those at University B. Research limitations/implications: The factors which affected the success of PBL using library e-resources have not been identified in this study, a task for a future qualitative research study. Practical implications: This study will both inspire the use of library e-resources in learning activities and promote ILSE. Originality/value: Integrating PBL with library e-resources provides opportunity to identify the advantages of library e-resources in supporting student ILSE, resulting a better learning achievement.
Keywords: Indonesian universities; Information literacy; Information literacy self-efficacy; Library e-resources; Problem-based learning; Self-efficacy